2020
DOI: 10.1186/s41938-020-00312-2
|View full text |Cite
|
Sign up to set email alerts
|

Screening, identification, and colonization of fungal root endophytes against Dematophora necatrix: a ubiquitous pathogen of fruit trees

Abstract: The goal of the present research was to ascertain the potential root endophytic fungi against Dematophora necatrix, Hartig, the causal pathogen of white root rot in apples; however, it has an expanded range of hosts across different fruit trees. Out of 36 endophytic fungi segregated from symptomless roots of apple, wheat, maize, marigold, cherry, and garlic plants, only 9 isolates showed inhibitory effect during preliminary screening and were further assayed under in vitro, pot, and field conditions against th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Root colonization assay revealed maximum endosphere and rhizosphere colonization with Crinipellis tabtim strain M8. Also, confocal microscopic illustrations of transverse sections of root cells tenanted by fungal endophytes Crinipellis tabtim strain M8 as compared to untreated control suggested the persistence and establishment of endophytes in the endosphere of apple seedlings, shown in Figure 1 [47].…”
Section: Exploitation Of Microbial Endophytes As Ard Management Strategymentioning
confidence: 96%
See 1 more Smart Citation
“…Root colonization assay revealed maximum endosphere and rhizosphere colonization with Crinipellis tabtim strain M8. Also, confocal microscopic illustrations of transverse sections of root cells tenanted by fungal endophytes Crinipellis tabtim strain M8 as compared to untreated control suggested the persistence and establishment of endophytes in the endosphere of apple seedlings, shown in Figure 1 [47].…”
Section: Exploitation Of Microbial Endophytes As Ard Management Strategymentioning
confidence: 96%
“…(a) Crinipellis tabtim strain M8. (b) Control by confocal laser scanning microscopy (CLSM by Pal et al[47]).…”
mentioning
confidence: 99%
“…Various fungal species have been used as biocontrol agents against R. necatrix (Table 1). These antagonistic fungi reduce mycelial growth in vitro and decrease disease symptoms caused by R. necatrix in different fruit tree crops such as apples, avocados, and apricots (Cruz et al, 2014;Pal et al, 2020;Ruano-Rosa et al, 2018). Among fungal genera investigated as biocontrol agents, Trichoderma has received considerable attention and has been successfully implemented as a BCA against R. necatrix in apple orchards (Golafrouz et al, 2020;Pasini et al, 2016;Sztejnberg et al, 1987) and avocado plants (Ruano Rosa and López-Herrera, 2009;Ruano-Rosa et al, 2018).…”
Section: Fungal Antagonistmentioning
confidence: 99%
“…Among fungal genera investigated as biocontrol agents, Trichoderma has received considerable attention and has been successfully implemented as a BCA against R. necatrix in apple orchards (Golafrouz et al, 2020;Pasini et al, 2016;Sztejnberg et al, 1987) and avocado plants (Ruano Rosa and López-Herrera, 2009;Ruano-Rosa et al, 2018). A recent study by Pal et al (2020) observed that the endophytic fungi Aspergillus aculeatus (strain C2) showed a maximum mycelial inhibition of 81.48%, and Crinipellis tabtim (strain M8) reduced disease incidence by up to 84.95% under field conditions in apple orchards. Furthermore, nonpathogenic R. necatrix isolates Rn12 and 29 have shown to successfully regulate R. necatrix pathogens (Arjona-López and López-Herrera, 2020).…”
Section: Fungal Antagonistmentioning
confidence: 99%
“…[ 16 , 17 , 18 ], Entoleuca sp. [ 19 , 20 ], non-pathogenic R. necatrix [ 21 ], Crinipellis tabtim or Fusarium equiseti [ 22 ]; antagonistic rhizobacteria, such as Pseudomonas spp. or Bacillus spp.…”
Section: Introductionmentioning
confidence: 99%